STRATEGI CONTENT MARKETING SUARA TELFON UNTUK MENINGKATKAN BRAND AWARENESS: STUDI KASUS CONTENT MARKETING AVOSKIN DI INSTAGRAM @SUARATELFON - Irdewanti, Erni; Setianti, Yanti (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
The increasing use of Instagram social media as a media promotion has made content creators have to compete so that their content continues to attract audiences. Suara Telfon offers content marketing service on their own Instagram account @suaratelfon with 200K followers as of May, 2023. This research aimed to (1) discover and define the implementation of content marketing strategy of Suara Telfon on building Avoskin’s brand awareness, (2) what factors could support and hinder the content marketing creation. The theory and concept used in this research are planning theory, content marketing concept by Kotler, and brand awareness. The research method is using qualitative research. The data are collected by qualitative interview and observation. The result of this research showed that the implementation of content marketing strategy by Suara Telfon is based on the 8 steps of content marketing by Kotler. They are goal setting, audience mapping, idea and content planning, content making, content distribution, content amplification, content evaluation, and content improvement. Suara Telfon conducted research on Instagram’s audience and algorithm that changes dynamically. Suara Telfon’s content marketing strategy has also succeeded on building Avoskin’s brand awareness at the brand recall level.